Assessment of Dietary Intake Patterns and Their Correlates among University Students in Lebanon - Salameh, Pascale; Jomaa, Lamis; Issa, Carine; Farhat, Ghada; Salamé, Joseph; Zeidan, Nina; Baldi, Isabelle, for the Lebanese National Conference for Health in University Research Group (Frontiers in Public Health, 2014)
Introduction: Unhealthy dietary habits are major risk factors for chronic diseases, particularly if adopted during early years of adulthood. Limited studies have explored the food consumption patterns among young adults in Lebanon. Our study aimed to examine common dietary patterns and their correlates among a large sample of university student population in Lebanon, focusing on correlation with gender and body mass index (BMI). Methods: A cross-sectional study was carried out on 3384 students, using a proportionate cluster sample of Lebanese students from both public and private universities. A self-administered food frequency questionnaire was used to assess dietary intake of university students. Factor analysis of food items and groups, cluster analysis of dietary patterns, and multivariate regressions were carried out. Results: Three dietary patterns were identified among university youth namely a vegetarian/low calorie dietary pattern (characterized mainly by consumption of plant-based food while avoiding “western” food, composite dishes, and bread); a mixed dietary pattern (characterized by high consumption of plant-based food, followed by composite dishes, bread, and a low consumption of western type food); and finally, a westernized dietary pattern (characterized by high consumption of white bread and western food, and a strong avoidance of plant food and composite dishes). We observed significant differences between males and females in terms of their reported food intake and dietary patterns. Females were particularly more prone to adopt the vegetarian/low calorie diet than males (ORa = 1.69; p < 0.001), while males were more likely to adopt a westernized diet (ORa = 1.51; p < 0.001), seemingly in private universities (p = 0.053). Students with high income and obese students (BMI ≥ 30 kg/m2) were more likely to consume vegetarian/low calorie diets (p < 0.05). Conclusion: Male university students reported a higher consumption of the westernized dietary pattern as compared to female university students in Lebanon, while the latter reported a higher adoption of a vegetarian diet. Health promotion programs are needed to address the dietary intakes and lifestyle behaviors of young adults in Lebanon to help prevent obesity and other associated comorbidities.